2019
DOI: 10.1177/0954407019859820
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism analysis of vehicle start-up judder based on gradient characteristic of Stribeck effect

Abstract: This paper presents a profound mechanism investigation for vehicle start-up judder phenomenon using a combination of experiment and simulation. First, from the experimental analysis, the characteristic frequency of start-up judder is mainly concentrated at about 9 Hz. A 13-degree-of-freedom powertrain branched model is established to numerically reproduce experimental phenomenon. The validity and accuracy of simulation model in reflecting the characteristics of start-up judder are verified by the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Previous studies have shown that the natural frequencies of each side of the clutch are excited separately during slipping of the clutch. 9,13 The undamped natural frequencies of the system are calculated by setting the applied torques and damping coefficients to zero. If the damping and loads are eliminated, the equations of motion for the driven side of the driveline can be written as…”
Section: System Natural Frequenciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the natural frequencies of each side of the clutch are excited separately during slipping of the clutch. 9,13 The undamped natural frequencies of the system are calculated by setting the applied torques and damping coefficients to zero. If the damping and loads are eliminated, the equations of motion for the driven side of the driveline can be written as…”
Section: System Natural Frequenciesmentioning
confidence: 99%
“…The only input in this mechanical system is the torque, which is applied from the engine based on equation (13). It depends on the engine speed.…”
Section: Vibrations Of the System During And After Clutch Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the limitation of tire–road adhesion coefficient, the torque from the driving tires is transformed into the longitudinal tractive force acting on the vehicle body ( m v ), which overcomes the resistance and makes the vehicle accelerate forward. For establishing the motion differential equations of the vehicle powertrain branched model, the method in the literature 22 is cited, as well as transient engine torque. The meanings and values for the symbols in Figures 3 and 4 are listed in Table 1 in Appendix 1.…”
Section: Simulation Analysis Of Vehicle Start-up Juddermentioning
confidence: 99%
“…The uneven contact pressure distributions along the radial direction have a slight influence on clutch judder, while the uneven contact pressure distributions along the circumference contribute to the judder substantially. Yuan and Wu 26 studied the vehicle start-up judder phenomenon using a combination of experiment and simulation. The influence of the negative gradient characteristic of friction coefficient was mainly analyzed numerically through a powertrain branched model.…”
Section: Introductionmentioning
confidence: 99%